Case From Practice Features of the Covid-19 Course with Concomitant Diseases (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
When studying the pathogenesis of a new coronavirus infection, hemorological disorders have a significant impact on the course and outcome of the disease. It is known that chronic diseases of the cardiovascular and respiratory system, concomitant infectious diseases lead to severe trends and complications of COVID-19. Consequently, in each case, each patient needs to study the interaction of various factors for the flow and outcome of the disease.Examine the activity of the hemochaguance system in one case of practitioners in a patient COVID-19 amid related diseases.Evaluation of the functions of the hemokoaguagulation system in one case of practitioners in a patient COVID-19 Against the background of concomitant diseases, the history of the disease of the patient retrospectively and promising was studied.Analyzed by a clinical case of one patient from practice. During the study, clinical manifestations and laboratory readings have a patient with COVID-19 described in detail. Despite the late treatment on the outpatient and inpatient stage, with the help of timely treatment, the rapid flow of the disease was suspended without complications to cure a patient with COVID-19.Patients with somatic diseases adding oral anticoagulants to the treatment regimen prevents unpleasant consequences and serious flow SARS-COV-2. Bearing in mind damage in different parts of the coagulation system of blood in the pathogenesis in patients with COVID-19, the purpose of adequate therapy with anticoagulants has a special place when treating patients.